Complex physical rehabilitation of first mature age women after arthroscopic operation about combined injury of meniscus and ligaments of knee joint in policlinic - Гончарук Наталія Володимирівна (Nataliia Goncharuk); Без’язична Ольга Володимирівна (Olga Bezyazychna); Дмитренко Оксана Андріївна (Oxana Dmytrenko) (Slobozhanskyi Herald of Science and Sport, 2014)
The purpose of the work is to work out and evaluate the proposed program of physical rehabilitation for women of basic group on the basis of study of dynamics of indexes of the locomotor apparatus, cardiovascular and respiratory systems, and common physical capacity for work. Material and methods: twenty four women of first mature age based of regional hospital of Kharkov were investigated in the research. Results: the effectiveness of the proposed program of physical rehabilitation is offered proved on the basis of study of the indexes dynamics of indexes of the locomotor apparatus, cardiovascular and respiratory systems, and common physical capacity for work. Conclusions: determined that the proposed program of physical rehabilitation for injured women of basic group was more effective